A influência do alongamento prévio no pico de torque e na taxa de desenvolvimento de força - Souza, Renata Helena de [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The objective of this study was to investigate the influence of previous active static stretch on the peak torque (PT) and rate of force development (TDF) during isokinetic concentric contractions at 60 and 180.s-1 in active individuals. Twelve active subjects with ages between 18 and 30 years participated of this study. The individuals were submitted in different days to the following tests: 1) Familiarization session to the isokinetic dynamometer; 2) Five maximal isokinetic concentric contractions for knee extensors at each angular velocity (60 and 180.s-1) to determine PT and TDF (Control), and; 3) Two active static stretching exercises for the dominant leg extensors (10 x 30 s for each exercise, with 20 s of rest). After the stretching, the isokinetic test was repeated (Post-Stretching). The conditions 2 and 3 were performed in random order. There was no significant modification after the stretch exercises on the PT, angle and time at which the PT was attained, at 60 and 180º.s-1. In the same way, there was no significant modification on the TDF and angle at which the maximal TDF was attained in both angular speeds. In other way, the time to attain maximal TDF (TTDF) at 180º.s-1 was significantly lower after the stretching (Pre - 98.3 ± 27.5 ms and Post - 86.6 ± 30.2 ms). There was significant modification on the torque (60 and 180º.s-1) and time (60º.s-1) at different delta of angle variations, obtained at 60º.s-1 at Control and Post-Stretching conditions. However, there was significant reduction of time after the stretching exercises on delta of angle variations of 90-88º (Pre - 46.6 ± 6.5 ms and Post - 44.1 ± 5.1 ms), 88-85º (Pre - 65.8 ± 7.9 ms and Post - 63.3 ± 4.9 ms) and 85-80º (Pre - 93.3 ± 7.7 ms and Post - 90.0 ± 4.2 ms) at 180º.s-1. With base on these data, it is possible to conclude that PT and TDF do not modify after static stretching, irrespectively on the speed...(Complete abstract click electronic access below)

O objetivo do presente estudo foi investigar em indivíduos ativos a influência do alongamento prévio estático ativo no pico de torque (PT) e na taxa de desenvolvimento de força (TDF) durante contrações isocinéticas concêntricas a 60 e 180.s-1. Participaram deste estudo 12 sujeitos ativos com idades entre 18 e 30 anos. Os indivíduos foram submetidos, em dias, diferentes aos seguintes protocolos: 1) Familiarização ao teste no dinamômetro isocinético; 2) Cinco contrações isocinéticas concêntricas máximas para os extensores do joelho em cada velocidade angular (60 e 180.s-1) para determinar o PT e a TDF (Controle), e; 3) Dois exercícios de alongamento para os músculos extensores do joelho da perna dominante (10 x 30 s para cada alongamento, com recuperação de 20 s). Após o alongamento, o teste isocinéticos foi repetido (Pós-Alongamento). As condições 2 e 3 foram realizadas em ordem aleatória. Não houve modificação significante após a realização dos exercícios de alongamento no PT, no ângulo e no tempo nos quais o PT foi atingido, a 60 e 180º.s-1. Do mesmo modo, não houve modificação significante na TDF e no ângulo no qual a TDF máxima foi alcançada em ambas as velocidades. Por outro lado, o tempo para a TDF máxima ser atingida (TTDF) a 180º.s-1 foi significantemente menor após o alongamento (Pré - 98,3 ± 27,5 ms e Pós - 86,6 ± 30,2 ms). Não houve modificação significante após a realização dos exercícios de alongamento no torque (60 e 180º.s-1) e no tempo (60º.s-1) em diferentes deltas de variação de ângulos, obtidos a 60º.s-1 nas condições Controle e Pós-Alongamento. Porém, houve redução significante do tempo após a realização dos exercícios de alongamento nos deltas de variação de ângulo 90-88º (Pré - 46,6 ± 6,5 ms e Pós - 44,1 ± 5,1 ms), 88-85º (Pré - 65,8 ± 7,9 ms e Pós - 63,3 ± 4,9 ms) e 85-80º... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Medicina esportiva; Exercicios; Força e flexibilidade; Força muscular; Flexibility; Muscular strenght; Exercise